Cancer Cell Detection‐Based on Released Hydrogen Peroxide Using a Non‐Modified Closed Bipolar Electrochemical System. Issue 16 (29th July 2020) - Shokouhi, Maryam; Mehrgardi, Masoud A.
Abstract : The Cover Feature shows a non‐modified bipolar electrochemical biosensor integrated with an electrochemiluminescence (BPE‐ECL) detection system, providing a simple and ultrasensitive tool for the early‐stage diagnosis of cancers. More information can be found in the Article by M. Shokouhi and M. A. Mehrgardi .